2017
DOI: 10.1177/0954406217700176
|View full text |Cite
|
Sign up to set email alerts
|

An analytical study of the scattering of ultrasonic guided waves at a delamination-like discontinuity in a plate

Abstract: Interface delaminations between individual plies in a composite, or disbonds of face sheets in honeycomb structures often remain undetected. Using guided ultrasonic waves (Rayleigh and Lamb waves) such hidden defects can be detected. In this work, an analytical framework that considers propagating, nonpropagating and evanescent waves to analyze the scattering of an incident ultrasonic wave at a delamination-like discontinuity is presented. Wave conversion at the interface of the damage is quantified in terms o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…In this case, the segment above the crack acts as a newly formed waveguide for Lamb waves. In this region, "wave trapping" occurs under certain conditions, i.e., only low transmission to other waves occurs at the trailing edge of the crack [6,19]. Depending on the excitation frequency and thickness of the core of the sandwich panel, it is shown that the segment below the defect also acts as a waveguide for either Lamb or Rayleighlike waves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the segment above the crack acts as a newly formed waveguide for Lamb waves. In this region, "wave trapping" occurs under certain conditions, i.e., only low transmission to other waves occurs at the trailing edge of the crack [6,19]. Depending on the excitation frequency and thickness of the core of the sandwich panel, it is shown that the segment below the defect also acts as a waveguide for either Lamb or Rayleighlike waves.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, scattering at defects is investigated through a number of different methods. If the discontinuity lies in a cross-sectional plane of the waveguide, e.g., for cracks perpendicular to the axial direction, the modal decomposition method can be applied [6,25,26]. For more complex damage geometries, a combination of finite element (FE) and boundary element techniques is suitable (e.g., see Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed by various research groups that Lamb wave scattering at the beginning and tip of defect is determined by its position. Schaal et al estimated frequency-dependent scattering coefficients for fundamental Lamb wave modes at both ends of the defect (Schaal et al 2017). Based on this approach, Hu proposed a technique to locate delamination defects based on reflection and transmission coefficients of A 0 and S 0 modes (Hu et al 2008).…”
Section: Guided Wave Interaction With Actual Structural Defectmentioning
confidence: 99%
“…Most conventional ultrasonic testing techniques utilized for testing plate-like structures take advantage of Lamb waves in one way or the other. [1][2][3][4] Lamb waves are guided waves that follow the boundaries of plate-like structures and can travel long distances without noticeable damping. 5 Lamb waves are dispersive, which means that their velocity is a function of frequency.…”
Section: Introductionmentioning
confidence: 99%